Parasitic infections of coyote, Canis latrans (Carnivora: Canidae) in a Costa Rican National park and a surrounding agricultural area [Infecciones parasitarias del coyote, Canis latrans (Carnivora: Canidae) en un Parque Nacional y una zona agrícola en Costa Rica] - Blanco-Peña, Kinndle (2012)
As human populations expand into wild habitats with their pets and livestock, the potential spread of disease to wildlife or vice versa increases. Because, wild and domestic canids may pose as reservoirs or disseminators of infectious diseases (including parasites), coyotes (Canis latrans) may also serve as indicators of ecological health. In Costa Rica, little information exists on coyote parasites, making research necessary to identify potential zoonotic interactions. For this reason, a survey of the coyote parasites was performed in a mixed area of protected woodland and agricultural land, surrounding Irazú Volcano National Park (IVNP) in Cartago, Costa Rica. Over a one-year period, 209 fecal samples were collected directly from the ground. Collection took place on a monthly basis in a trail sectioned into three sub-areas named Irazú (closest to the volcano), potato fields (where potatoes were cultivated), and Prusia (a protected sector of IVNP). Sectioning the trail allowed separate collection and analysis of the samples, where 99 were obtained from Irazú, 11 from potato fields and 99 from Prusia. Using direct examination and mechanical concentration 36.84% positive samples containing at least one helminth were found. The presence of parasites was similar for both woodland areas (33.3% in Prusia and 37.4% in Irazú), but differed from the 63.6% observed in the potato fields. Hookworm parasites (probably Ancylostoma caninum), threadworms (possibly Strongyloides sp.), Toxocara canis, Trichuris sp. and Taenia pisiformis were identified, as well as Hymenolepis diminuta, possible spurious parasite resulting from the ingestion of rodents by coyotes. Seasonal details are discussed, concluding that wet and dry seasons affect presence of parasites. Some remarks are made on the importance of these first findings for Costa Rica, especially considering the systematic way in which the collection of samples was carried out.